Differential role of MAX2 and strigolactones in pathogen, ozone, and stomatal responses. (28th February 2020) - Kalliola, Maria; Jakobson, Liina; Davidsson, Pär; Pennanen, Ville; Waszczak, Cezary; Yarmolinsky, Dmitry; Zamora, Olena; Palva, E. Tapio; Kariola, Tarja; Kollist, Hannes; Brosché, Mikael
Abstract: Strigolactones are a group of phytohormones that control developmental processes including shoot branching and various plant–environment interactions in plants. We previously showed that the strigolactone perception mutant more axillary branches 2 (max2) has increased susceptibility to plant pathogenic bacteria. Here we show that both strigolactone biosynthesis ( max3 and max4 ) and perception mutants ( max2 and dwarf14 ) are significantly more sensitive to Pseudomonas syringae DC3000. Moreover, in response to P. syringae infection, high levels of SA accumulated in max2 and this mutant was ozone sensitive. Further analysis of gene expression revealed no major role for strigolactone in regulation of defense gene expression. In contrast, guard cell function was clearly impaired in max2 and depending on the assay used, also in max3, max4, and d14 mutants. We analyzed stomatal responses to stimuli that cause stomatal closure. While the response to abscisic acid (ABA) was not impaired in any of the mutants, the response to darkness and high CO2 was impaired in max2 and d14‐1 mutants, and to CO2 also in strigolactone synthesis ( max3, max4 ) mutants. To position the role of MAX2 in the guard cell signaling network, max2 was crossed with mutants defective in ABA biosynthesis or signaling. This revealed that MAX2 acts in a signaling pathway that functions in parallel to the guard cell ABA signaling pathway. We propose that the impaired defense responses of max2 are related to higher stomatal conductance that allows increased entry of bacteria or air pollutants like ozone. Furthermore, as MAX2 appears to act in a specific branch of guard cell signaling (related to CO2 signaling), this protein could be one of the components that allow guard cells to distinguish between different environmental conditions.